Urban planning after war, disaster and disintegration case studies - Yarwood, John R.
This book concerns the relationship between urban planning (and similar things) on the one hand, and war, natural disaster and societal or political disintegration on the other. The supposition is that one may mitigate the other. The book recounts the authors professional experience of specific cases of disaster (earthquake and flood) in the Philippines, war in Bosnia, Afghanistan and South Sudan, and disintegration in Albania and Ireland. He identifies the key themes in urban and regional planning which these case studies illustrate. The themes include (a) the delivery of building land with site preparation, infrastructure and property rights; (b) the size and amount of plots able to match both demographic projections and wealth distribution; (c) the creation of a property market able to deliver affordable land and buildings to match demand, encourage investment and further the development of the economy; (d) the spatial or geographic adjustment of institutional patterns to reflect the components of identitymaking for fuzzy sovereignty; (e) a form of organisation which leads to effective project management and implementation, and so on. The view is taken that lack of suitable development land supply, a land market unable to deliver affordable property to the people and unable to support economic growth, and a spatial-institutional pattern unable to match key aspects of identity, are all causes of war as well as societal or political decline